2017
DOI: 10.1124/mol.116.108100
|View full text |Cite
|
Sign up to set email alerts
|

Statins Attenuate Activation of the NLRP3 Inflammasome by Oxidized LDL or TNFα in Vascular Endothelial Cells through a PXR-Dependent Mechanism

Abstract: Excessive activation of the NLRP3 inflammasome is implicated in cardiovascular diseases. Statins exert an anti-inflammatory effect independent of their cholesterol-lowering effect. This study investigated the potential role of statins in the activation of the NLRP3 inflammasome in endothelial cells (ECs). Western blotting and quantitative reverse-transcription polymerase chain reaction showed that oxidized low-density lipoprotein (ox-LDL) or tumor necrosis factor α (TNF) activated the NLRP3 inflammasome in ECs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 43 publications
2
49
0
1
Order By: Relevance
“…Duewell et al () showed that deficiency of inflammasome‐related molecules, such as NLRP3, ASC, or IL‐1β, attenuated the development of atherosclerotic lesions in mice, indicating that NLRP3 inflammasomes, induced by cholesterol crystals, play an important role in the progression of atherosclerosis. In addition to macrophages, cholesterol crystals also markedly increase the formation and activation of NLRP3 inflammasomes in carotid arterial endothelial cells, as shown by increased colocalization of NLRP3 with ASC or caspase‐1, enhanced caspase‐1 activity, and elevated IL‐1β secretion in mice (Koka et al, ), suggesting an essential role for endothelial inflammasome activation in arterial dysfunction and atherosclerosis (S. Wang et al, ).…”
Section: Nlrp3 Inflammasome Activation By Endogenous Crystalline Molementioning
confidence: 99%
“…Duewell et al () showed that deficiency of inflammasome‐related molecules, such as NLRP3, ASC, or IL‐1β, attenuated the development of atherosclerotic lesions in mice, indicating that NLRP3 inflammasomes, induced by cholesterol crystals, play an important role in the progression of atherosclerosis. In addition to macrophages, cholesterol crystals also markedly increase the formation and activation of NLRP3 inflammasomes in carotid arterial endothelial cells, as shown by increased colocalization of NLRP3 with ASC or caspase‐1, enhanced caspase‐1 activity, and elevated IL‐1β secretion in mice (Koka et al, ), suggesting an essential role for endothelial inflammasome activation in arterial dysfunction and atherosclerosis (S. Wang et al, ).…”
Section: Nlrp3 Inflammasome Activation By Endogenous Crystalline Molementioning
confidence: 99%
“…These types of modified LDL mimic damageand pathogen-associated molecular patterns, thus serving as the primary sources of cholesterol accumulation and chronic inflammation in atherosclerotic plaques (Tabas et al, 2015). In addition, these modified LDLs can cause oxidative stress, inflammation, NLRP3 inflammasome activation, and immune response, thus amplifying the vicious cycle of atherogenic cellular events (Steinberg and Witztum, 2010;Wang et al, 2017h). In addition to modified LDL, interleukin 1 (IL-1) (IL-1a and IL-1b) also drives vascular inflammation, with IL-1a mainly being involved in arterial remodeling during the early phase of atherosclerosis, whereas IL-1b drives inflammation and atheroprogression to advanced state of atherosclerosis (Vromman et al, 2019).…”
Section: Atherosclerosis: An Introductionmentioning
confidence: 99%
“…For example, PXR in early cancer development could function in an opposite manner when compared in late cancer activation. This kind of behavior is seen with inflammasomes (e.g., NLRP3) [ 80 , 81 , 82 , 83 ]. Differences in outcome-specific PXR activation is also possible, for example, PXR inhibits inflammation and inflammation-induced colitis [ 84 ], but promotes late sporadic colon cancer [ 15 ].…”
Section: Discussionmentioning
confidence: 99%